El sistema de la gradación en latín: noción básica, estructura y usos - Suárez Martínez, Pedro Manuel (1996)
In front of the traditional and modern theories which see two grammatical categories in the latin gradation, we shall suggest in this paper the existence of just one grammatical category, whose basic notion is not the idea of comparison but that of elation. In the light of this assumption, we shall propose a structure which permits us to explain satisfactorily all the ses of the degrees, even those which seem to be anomalous.
Keywords: Lengua latina; Filología latina